Ankle and Foot: Focus on Inflammatory Disease - Giraudo, Chiara; Fichera, Giulia; Ganguly, Sujata; Arumugam, Moorthy; Cecchin, Diego; Rennie, Winston J. (Seminars in Musculoskeletal Radiology, 2023)
The ankle and foot have numerous bones and complex joints that can be affected by several types of inflammatory arthritis with different patterns and various radiologic signs, depending on the phase of the disease. Involvement of these joints is most frequently seen in peripheral spondyloarthritis and rheumatoid arthritis in adults and juvenile idiopathic arthritis in children. Although radiographs are a mainstay in the diagnostic process, ultrasonography and especially magnetic resonance imaging allow early diagnosis and are crucial diagnostic tools. Some diseases have typical features based on target populations (e.g., adults versus children, men versus women), but others may have overlapping imaging characteristics. We highlight key diagnostic features and describe appropriate investigations to guide clinicians toward the correct diagnosis and provide support during disease monitoring.
Keywords: inflammatory diseases; foot; ankle; imaging